DDIS-12. ONC201: THE FIRST SELECTIVE, NON-COMPETITIVE DRD2/3 ANTAGONIST FOR CLINICAL NEURO-ONCOLOGY. (5th November 2018) - Vijay Prabhu, Varun; Madhukar, Neel; Anantharaman, Lakshmi; Sulli, Chidananda; Davidson, Edgar; Deacon, Sean; Tarapore, Rohinton; Rucker, Joseph; Charter, Neil; Doranz, Benjamin; Oster, Wolfgang; Stogniew, Martin; et al.
Abstract: ONC201 has exhibited preliminary clinical evidence of anti-tumor activity and safety in high grade glioma patients. In this study, we identified and characterized a previously unknown binding target of ONC201. BANDIT – a machine learning-based target identification platform – predicted that ONC201 would bind with high selectivity to the G-protein coupled receptors (GPCRs) dopamine receptor D2(DRD2) and D3 (DRD3). DRD2 is overexpressed in glioma, controls pro-survival mechanisms, and its antagonism causes glioma apoptosis. β-arrestin and cAMP assays determined that ONC201 selectively antagonizes DRD2/3. Consistent with BANDIT and in contrast to antipsychotics that antagonize DRD2, ONC201 did not antagonize other dopamine receptors or other GPCRs. Schild analyses and radioligand competition assays revealed DRD2 antagonism at concentrations consistent with ONC201 anticancer activity. In accordance with superior selectivity, ONC201 exhibited a wider therapeutic window compared to antipsychotics. Combined DRD2/DRD1 inhibition was found to be inferior to DRD2 inhibition alone, suggesting that selectively targeting D2-like receptors yields superior anti-cancer efficacy. ONC201 exhibited a very slow association rate for DRD2 relative to antipsychotics, whereas the dissociation rate was similar to atypical antipsychotics that do not cause extrapyramidal symptoms. Alanine scanning mutagenesis of DRD2 identified 6 residues that are critical for ONC201-mediated antagonism of DRD2 and located in orthosteric and allosteric sites. Molecular docking revealed orthosteric interactions at TM-II and an allosteric interaction at the interface of TM-IV and –V that mediates the DRD2 homodimer interface. These orthosteric and allosteric interactions exhibited predicted affinities associated with the observed competitive and non-competitive effects, respectively, and point mutations at either site increased the Ki of ONC201 in competition assays with radiolabeled methyl-spiperone. In summary, we identify both non-competitive and competitive antagonism of DRD2 by ONC201 that may explain its unique selectivity, safety, and anti-cancer activity in clinical trials as the first compound to target this receptor for oncology.